Meaning of leprosy for people who have experienced treatment during the sulfonic and multidrug therapy periods - Karen da Silva Santos; Cinira Magali Fortuna; Fabiana Ribeiro Santana; Marlene Fagundes Carvalho Gonçalves; Franciele Maia Marciano; Silvia Matumoto (Universidade de São Paulo, 2015)
AbstractObjective: to analyze the meanings of leprosy for people treated during the sulfonic and multidrug therapy periods.Method: qualitative nature study based on the Vigotski's historical-cultural approach, which guided the production and analysis of data. It included eight respondents who have had leprosy and were submitted to sulfonic and multidrug therapy treatments. The participants are also members of the Movement for Reintegration of People Affected by Leprosy.Results: the meanings were organized into three meaning cores: spots on the body: something is out of order; leprosy or hanseniasis? and leprosy from the inclusion in the Movement for Reintegration of People Affected by Leprosy.Conclusion: the meanings of leprosy for people submitted to both regimens point to a complex construction thereof, indicating differences and similarities in both treatments. Health professionals may contribute to the change of the meanings, since these are socially constructed and the changes are continuous.